(untitled) (Altre Modernità, 2024)
The integration of digital technology into language teaching has profoundly changed the educational landscape, bringing with it both, benefits and challenges. This essay explores the impact of these innovations, analysing the role of digital tools in enhancing language learning, their potential for greater accessibility and student engagement, and the need for teachers to adapt their methods, to make effective use of them. In an increasingly digitalized world, language skills now include media skills. After reviewing the main national and international background documents on the subject, the author defines and classifies language technologies and presents some state-of-the-art digital tools for language teaching. Digital literacy concerns both the learner and the teacher. A blended learning university training model for future teachers of German as a foreign language is then presented, which has been successfully in place for some years at the University of Milan in collaboration with the Goethe-Institut. Finally, the essay concludes with some reflections on the future of foreign language teaching.